Use of a common European approach for nanomaterials' testing to support regulation: a case study on titanium and silicon dioxide representative nanomaterials. Issue 11 (30th June 2020) - Zijno, Andrea; Cavallo, Delia; Di Felice, Gabriella; Ponti, Jessica; Barletta, Bianca; Butteroni, Cinzia; Corinti, Silvia; De Berardis, Barbara; Palamides, Jessica; Ursini, Cinzia L.; Fresegna, Anna M.; Ciervo, Aureliano; et al.
Abstract: The European Union (EU) continuously takes ensuring the safe use of manufactured nanomaterials (MNMs) in consumer products into consideration. The application of a common approach for testing MNMs, including the use of optimized protocols and methods' selection, becomes increasingly important to obtain reliable and comparable results supporting the regulatory framework. In the present study, we tested four representative MNMs, two titanium dioxides (NM100 and NM101) and two silicon dioxides (NM200 and NM203), using the EU FP7‐NANoREG approach, starting from suspension and dispersion preparations, through to their characterization and final evaluation of biological effects. MNM dispersions were prepared following a refined NANOGENOTOX protocol and characterized by dynamic light scattering (DLS) in water/bovine serum albumin and in media used for in vitro testing. Potential genotoxic effects were evaluated on human bronchial BEAS‐2B cells using micronucleus and Comet assays, and pro‐inflammatory effects by cytokines release. Murine macrophages RAW 264.7 were used to detect potential innate immune responses using two functional endpoints (pro‐inflammatory cytokines and nitric oxide [NO] production). The interaction of MNMs with RAW 264.7 cells was studied by electron microscopy. No chromosomal damage and slight DNA damage and an oxidative effect, depending on MNMs, were observed in bronchial cells. In murine macrophages, the four MNMs directly induced tumor necrosis factor α or interleukin 6 secretion, although at very low levels; lipopolysaccharide‐induced NO production was significantly decreased by the titania and one silica MNM. The application of this approach for the evaluation of MNM biological effects could be useful for both regulators and industries. Abstract : A harmonized approach was used to evaluate the biological effects of two titania and two silica representative MNMs. Potential toxicity was investigated on human bronchial cells and murine macrophages using in vitro methods. MNMs dispersions, prepared according to a NANoREG refined NANOGENOTOX protocol, were characterized by DLS analysis. Cyto‐genotoxic and inflammatory effects on human bronchial cells, and immunotoxicity and cellular uptake on murine macrophages were evaluated. The findings show that this approach could be a useful tool for regulators and industry.